2009
DOI: 10.1007/s10593-010-0447-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of new 2-[(3-aminopropyl)dimethyl-silyl]-5-trialkylgermylfurans

Abstract: New highly cytotoxic 3-aminopropyl derivatives of 2-dimethylsilyl-5-trialkylgermylfuran (IC 50 1−3 µg⋅ml −1 ) have been prepared by hydrosilylation of heterocyclic N-allylamines with the corresponding hydrosilane in the presence of Speier's catalyst. The influence of the amine structure and alkyl substituent at the germanium atom on the cytotoxicity has been investigated.The heterocyclic amines are important building blocks for the creation of anticancer drugs [1, 2]. In some cases the benzene ring has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Silylpropylamino derivatives of diethoxymethylfuran 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 have a certain cytoselectivity: compounds of this type exhibited high cytotoxicity to MG‐22 tumor cell lines (compounds 9 and 12 are an exception) and at the same time they were less toxic to HT‐1080. It should be noted that compounds with the phenyl substituent in position 5 of the furan ring generally have more pronounced cytotoxic activity on tumor cell lines compared to the analogues with Et 3 Si group and Et 3 Ge group in the furan ring . Morpholino derivative 19 is the more promising compound among the studied amines: moderate toxicity (LD 50 659 mg kg −1 ), high cytotoxicity on both cancer cell lines (IC 50 1–3 µg ml −1 ) and low cytotoxicity on normal fibroblasts (IC 50 60 µg ml −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silylpropylamino derivatives of diethoxymethylfuran 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 have a certain cytoselectivity: compounds of this type exhibited high cytotoxicity to MG‐22 tumor cell lines (compounds 9 and 12 are an exception) and at the same time they were less toxic to HT‐1080. It should be noted that compounds with the phenyl substituent in position 5 of the furan ring generally have more pronounced cytotoxic activity on tumor cell lines compared to the analogues with Et 3 Si group and Et 3 Ge group in the furan ring . Morpholino derivative 19 is the more promising compound among the studied amines: moderate toxicity (LD 50 659 mg kg −1 ), high cytotoxicity on both cancer cell lines (IC 50 1–3 µg ml −1 ) and low cytotoxicity on normal fibroblasts (IC 50 60 µg ml −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we studied the synthesis and cytotoxic activity of 2‐[(3‐aminopropyl)‐dimethylsilyl]‐5‐trialkylsilyl(germyl)furans . Our investigations have demonstrated that these types of compounds have high cytotoxic activity on two cell tumor lines, viz.…”
Section: Introductionmentioning
confidence: 91%
“…[4] On the other hand, heterocyclic amines are important structural fragments in many medicinal preparations. [5,6] The analysis of antitumor substances has shown that the introduction of a heterocyclic amino group leads to an increase in the solubility and the bioavailability of the active substance.Our previous investigations have demonstrated [7][8][9] that 3-[dimethyl(5-trialkylsilyl(gemyl)furan-2-yl)silyl]propylamines and 3-[(methyl)bis(5-trialkylsilylfuran-2-yl)silyl]propylamines possess promising cytotoxic activity accompanied by high toxicity and cytotoxicity to normal cells. To improve the cycloselectivity of this class of compounds and to reduce their toxcicity we decided to prepare a novel series of furylpropylamines, which contain a silacycle and an organosilicon or -germanium substituent in the furan ring in a single molecule and to study the cytotoxicity of the obtained compounds and estimate the effect of the silacycle, nature of the amine, and the type of element-organic substituent on the cytotoxicity.The starting 2-substituted furylhydrosilane 1 was prepared from furan by reaction with butyllithium, followed by addition of 1-chlorosilinane, 2,5-substituted furylhydrosilanes 2-5 have been prepared from substituted furans in a similar way.…”
mentioning
confidence: 99%
“…Our previous investigations have demonstrated [7][8][9] that 3-[dimethyl(5-trialkylsilyl(gemyl)furan-2-yl)silyl]propylamines and 3-[(methyl)bis(5-trialkylsilylfuran-2-yl)silyl]propylamines possess promising cytotoxic activity accompanied by high toxicity and cytotoxicity to normal cells. To improve the cycloselectivity of this class of compounds and to reduce their toxcicity we decided to prepare a novel series of furylpropylamines, which contain a silacycle and an organosilicon or -germanium substituent in the furan ring in a single molecule and to study the cytotoxicity of the obtained compounds and estimate the effect of the silacycle, nature of the amine, and the type of element-organic substituent on the cytotoxicity.…”
mentioning
confidence: 99%
“…2-(Aminopropyl)-dimethylsilyl-5-trialkylsilyl(germyl)furans also show a high cytotoxicity towards tumor cells [24,25].…”
mentioning
confidence: 99%